Clinical Features and Liver Biochemical Activity of Hepatitis A - S. Zuraida Zulkarnain; Anna Tjandarjani; Arwin P. Akib (Indonesian Pediatric Society, 1999)
A descriptive, cross sectional study, was conducted between January 1st 1993 until June 30th 1998. The objective of the study is to describe clinical features and liver biochemical activity of hepatitis A. Ninety three cases of hepatitis A (55,0%) were colleed from hospitalized acute viral hepatitis. Only 92 cases were evaluated, becuse no initial data was found in one case. The highest number of cases (44.5%) was in the age group of 5-10 years, 53 cases (57.6%) were boys and 39 cases (42.4%) were girls. From the history of illness 82 cases (89: 1 %) with jaundice, 60-80% with fever, nausea, vomiting, and anorexia. Abdominal pain and weakness in 35%, less than 12% wlth headache, myalgia, diarrhea, common cold and cough. Fifty cases (54.3%) were underweight based on weight for age. From physical examination 89.1% of cases showed Jaundice, 68.5% hepatomegaly, 23.9% abdominal tenderness, 18.5% fever, 6.5% splenomegaly, 5% pale, and 1.1% unconscious. Test of biochemical activity showed wide range result, AST 22-2869 IU/L, ALT 22-2880 IU/L, conjugated bilirubin 0.07-20.27 mg/dL and unconjugated bilirubin 0.14-11.89 mg/dL. Prolonged cholestatic, fulminant hepatitis and anerma were found in less than 3.2% of cases.